Rethinking al-Singkili’s Islamic Cosmology - Siraj, Fuad Mahbub; Syadli, Muhammad (KALAM, 2021)
The conception of universe has been one of the significant subjects discussed in the Qur'an. Verses of Qur’an have always encouraged human beings to observe and reflect upon on the creation of universe, seen in Islamic teachings as a sign of God's existence and power. Cosmology is a discipline that concerns about the origin of universe. In Islam, this topic has been a heated debate that comes with deeply theological consequences, in terms of tawhid (belief in God). This research is a library research with using a historical approach to obtain data and conducting content analysis. This research aims to explain further the concept of Islamic cosmology of ‘Abd al-Ra’ūf al-Singkili, an Indonesian philosophical sufi master and thinker. Al-Singkili begins his conception of cosmology by focusing on the definition of universe. This study finds out that he defined universe as all things other than al-Ḥaqq. Universe is created by Allah as a sign to know His Existence. Al-Singkili stated that the universe was not created from nothing to being (creatio ex nihillo), but rather through an emanation (fayḍ). In explaining the concept of emanation, al-Singkili used two terms, namely "fixed entity" (al-a’yān al-ṡābitah) and "potential entity" (al-a’yān al-khārijiyyah). Both potentials, according to him, are a shadow of God. The fixed entity is a direct shadow of God, while the potential entity is a shadow of the fixed entity. So, it can be concluded that everything other than God (nature) comes from Him, and its existence depends on the His being.